(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
By the end of the Middle English period, there is already considerable loss of inflectional morphology, and in Early Modern English, we see the last reflexes of a shift from synthetic Old English to analytic Modern English. In fact, the inflectional system of Early Modern English is not very different from what we have today. The changes in inflection that take place between 1500 and 1700 show marked sociolinguistic differentiation and are the subject of well-known case studies in sociohistorical linguistics. The derivational morphology of Early Modern English, onthe other hand, is considered to demonstrate much more wholesale and radical changein the form of new Latin prefixes and suffixes reanalyzed from borrowed lexis. Therate of integration of these word-formation processes is not, however, very uniform,and capturing this diversity is a major aim of this survey.